Aerobe Fermentation Enhanced Antioxidant Activity Index of Citrus limon Leaves - Herlina, Santi; Setiawansyah, Arif; Hidayati, Nurul (Journal of Food and Pharmaceutical Sciences, 2024)
The chemical composition and antioxidant activity of a natural product are directly correlated with the preparation process which can alter certain enzymatic pathways, leading to the alteration of the production of secondary metabolites affecting its biological activity. This study aims to observe the effects of the pre-extraction process of Citrus limon on its TFC, TPC, and antioxidant activity. Samples were prepared by two different pre-extraction techniques (solar drying and aerobe fermentation) and extracted using ultrasound-assisted extraction with ethanol 96%. The TFC and TPC were measured by a colorimetric method using a spectrophotometer UV-Vis. The antioxidant activity was tested on DPPH and calculated as AAI with ascorbic acid as a standard. The result showed that solar dried sample exhibited higher TFC and TPC than the fermented sample with TFC and TPC values of 32.165 mg QE/g and 335.80 mg GAE/g extract. In contrast, the antioxidant activity assay revealed that fermented samples provided higher antioxidant activity than solar-dried samples and even better than ascorbic acid with an IC50 value of 2.52 µg/mL. The pre-extraction process significantly influences the TFC, TPC and antioxidant activity of Citrus limon.